2016
DOI: 10.4236/me.2016.714145
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Tax Evasion: Empirical Evidence from Ghana

Abstract: For decades, researchers of tax systems and taxation as a whole are in a dilemma on the factors affecting taxpayers' noncompliant behaviors. Numerous experimental and survey results concluded by tax researchers have identified characteristics of noncompliant taxpayers because tax revenues are seen as a major source of income in funding government expenditures. Globalization has called for a huge demand for numerous public services thereby forcing governments into increasing tax revenues to finance these projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 11 publications
1
31
0
3
Order By: Relevance
“…Tanzi (1983) provides an empirical evidence on the impact of tax rates on tax evasion and concluded that the tax rateevasion experience varies in results from neutral effect to significantly positive and negative effect. In contrast to this view, some studies (Slemrod et al, 2000;Allingham et al, 1972) including most recent studies (Ameyaw et al, 2016) have concluded that there exists a statistically significant positive effect of tax rates on tax evasion.…”
Section: Effect Of Traditional Factors On Tax Evasionmentioning
confidence: 89%
See 4 more Smart Citations
“…Tanzi (1983) provides an empirical evidence on the impact of tax rates on tax evasion and concluded that the tax rateevasion experience varies in results from neutral effect to significantly positive and negative effect. In contrast to this view, some studies (Slemrod et al, 2000;Allingham et al, 1972) including most recent studies (Ameyaw et al, 2016) have concluded that there exists a statistically significant positive effect of tax rates on tax evasion.…”
Section: Effect Of Traditional Factors On Tax Evasionmentioning
confidence: 89%
“…However most of these studies are done in developed economise (Clotfelter, 1983;Klovland, 1984;Schneider et al, 2008) with a limited number focused on developing countries. Very few studies discuss the subject matter in the developing countries such as Ameyaw and Dzaka (2016) and Ameyaw et al (2015). Although non-compliance by tax payers is a continual and global problem, many indicators suggest that developing countries in sub-Saharan Africa have had the hardest hit (Annan et al, 2010).…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
See 3 more Smart Citations